Exploring Pedagogical Reflection through Video-Based Peer Review in EFL Microteaching - Ekawati, Yulia Nur; Prihatini, Fajar (Jurnal Bahasa Inggris, 2025)
Pedagogical reflection is widely recognized as an essential component of teacher professional development; however, reflective practices in EFL microteaching contexts often remain superficial and largely memory-based. Recent advances in video technology and peer review pedagogy offer promising opportunities to support deeper, evidence-informed reflection. This qualitative case study investigates how EFL pre-service teachers engage in pedagogical reflection through video-based peer review in a microteaching course and examines the challenges they encounter during the reflective process. The study was conducted in a blended microteaching course within an undergraduate English education program in Indonesia and involved 20 EFL pre-service teachers. Data were collected from teaching videos, reflective journals, peer feedback texts, and semi-structured interviews, and analyzed using thematic analysis. The findings reveal that video-based peer review supports pedagogical reflection as a gradual and developmental process. Through repeated engagement with teaching videos and peer feedback, pre-service teachers progressed from descriptive noticing of teaching practices to analytical reconsideration of pedagogical decisions and critical planning for instructional improvement. Teaching videos functioned as concrete reflective artifacts that grounded reflection in observable evidence, while peer feedback fostered reflective dialogue and exposure to alternative instructional perspectives. At the same time, several challenges were identified, including emotional discomfort when watching teaching videos, uncertainty in providing critical peer feedback, and practical constraints such as time demands and technical issues. Overall, the study suggests that video-based peer review can effectively enhance pedagogical reflection in EFL microteaching when supported by intentional instructional design, reflective scaffolding, and a supportive learning environment.